Physico-phytochemical Evaluation of Aqueous extract of Mamajjaka - Tanna, Samir (International Journal of Pharmaceutical & Biological Archive, 2010)
Mamajjaka (Enicostemma littorale auct. non Bl) is a well-known folklore medicine for the treatment of Madhumeha (Diabetes Mellitus). The drug has been attribute with other therapeutic potentials like antihelmintic, anti-inflammatory, hepatoprotective, antiperiodic etc. In present study analytical profile of aqueous extract (Ghana) of Mamajjaka is carried out with all the available methods including Microbial count, Heavy metal analysis and High performance thin layer chromatographic study. The generated information of the present study will provide data which is helpful in the identification and authentification of the drug Mamajjaka aqueous extract.